Privacy and the role of international law in the digital age - Yilma, Kinfe (Oxford : Oxford University Press, 2023)
Examines the role of international law in securing privacy and data protection in the digital age, considering the impact of the boundaries of international privacy law, and the potential of global privacy initiatives.
Also issued in print: 2023.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from PDF title page (viewed on February 2, 2023).
Keywords: Privacy, Right of; Data protection -- Law and legislation; Law; Laws of specific jurisdictions & specific areas of law